Simulation as a tool in studying payment and settlement systems - Leinonen, Harry (Henry Stewart Talks, 2010)
Modern payment systems are highly complex with numerous interdependencies, hidden risks and other characteristics, Simulation techniques have proved to be a good tool for analyzing many dimensions of payment and settlement systems and networks which are outside the reach of traditional calculus, The most common payment system simulation setups are presented together with concrete examples